Glycoprotein alpha-amylase inhibitor from Withania somnifera differentially inhibits various alpha-amylases and affects the growth and development of Tribolium castaneum - Kasar, Sainath S.; Marathe, Kiran R.; Bhide, Amey J.; Herwade, Abhijeet P.; Giri, Ashok P.; Maheshwari, Vijay L.; Pawar, Pankaj K. (PEST Management Science, 2017)
BACKGROUND: Identification and characterisation of plant defensive molecules enrich our resources to design crop protection strategies. In particular, plant-derived proteinaceous inhibitor(s) of insect digestive enzymes appear to be a safe, sustainable and attractive option. RESULTS: A glycoprotein having non-competitive alpha-amylase inhibitory activity with a molecular weight of 8.3 kDa was isolated and purified from seeds of Withania somnifera alpha-amylase inhibitor (WSAI). Its mass spectrometry analysis revealed 59% sequence coverage with Wrightide II-type alpha-amylase inhibitor from Wrightia religiosa. A dose-dependent inhibition of alpha-amylases from Aspergillus oryzae, Bacillus subtilis, Helicoverpa armigera and Tribolium castaneumwas recorded. Interestingly, WSAI did not inhibit human salivary alpha-amylase significantly. When adults of T. castaneum were fed with WSAI (1.6mg g(-1)), decrease inconsumption, growthandefficiency of conversion of ingested foodwas evident, along withover fourfold increases in feedingdeterrence index. Adecline inlarval residual alpha-amylase activity after feedingofWSAI resulted ina reduction in longevity of T. castaneum. CONCLUSION: The study reflects the significance of WSAI in affecting the overall growth and development of T. castaneum. Pre-and post-harvest pest resistive capability makes WSAI a potential candidate for insect pest management. Further, the effectiveness of this inhibitor could be explored either in formulations or through a transgenic approach. (C) 2016 Society of Chemical Industry